Berry flavonoids are differently modulated by timing and intensities of water deficit in Vitis vinifera L. cv. Sangiovese - Palai, Giacomo; Caruso, Giovanni; Gucci, Riccardo; D’Onofrio, Claudio (Frontiers in Plant Science, 2022)
In this work, we tested the effect of different regulated deficit irrigation (RDI) regimes on berry flavonoid content and its relative biosynthetic pathways. Vines were subjected to six irrigation regimes over two consecutive years: a) full irrigation during the entire irrigation period (FI); b) moderate (RDI-1M) or c) severe (RDI-1S) water deficit between berry pea-size and veraison; d) severe water deficit during the lag-phase (RDI-LS); and e) moderate (RDI-2M) or f) severe (RDI-2S) water deficit from veraison through harvest. Berries from both RDI-1 treatments showed the highest accumulation of anthocyanins, upregulating the expression of many genes of the flavonoid pathway since the beginning of veraison until harvest, far after the water deficit was released. Although to a lesser degree than RDI-1, both post-veraison water deficit treatments increased anthocyanin concentration, particularly those of the tri-substituted forms, overexpressing the F3′5′H hydroxylases. The moderate deficit irrigation treatments enhanced anthocyanin accumulation with respect to the severe ones regardless of the period when they were applied (pre- or post-veraison). The water deficit imposed during the lag-phase downregulated many genes throughout the flavonoid pathway, showing a slight reduction in anthocyanin accumulation. The measurements of cluster temperature and light exposure highlighted that under deficit irrigation conditions, the effects induced by water stress prevailed over that of light and temperature in regulating anthocyanin biosynthesis. Flavonol concentration was higher in RDI-1S berries due to the upregulation of the flavonol synthases and the flavonol-3-O-glycosyltransferases. In this case, the higher cluster light exposure induced by water deficit in RDI-1S berries had a major role in flavonol accumulation. We conclude that the timing and intensity of water stress strongly regulate the berry flavonoid accumulation and that proper management of deficit irrigation can modulate the phenylpropanoid and flavonoid pathways.